Management of patients with seasonal allergic rhinitis: Diagnostic consideration of sensitization to non‐frequent pollen allergens. Issue 8 (4th October 2021) - Höflich, Conny; Balakirski, Galina; Hajdu, Zuzanna; Baron, Jens Malte; Fietkau, Katharina; Merk, Hans F.; Strassen, Ulrich; Bier, Henning; Dott, Wolfgang; Mücke, Hans‐Guido; Straff, Wolfgang; Wurpts, Gerda; et al.
Abstract: Background: Diagnosis of pollen allergies is mainly based on test allergens for skin prick testing. In the minimum battery of test inhalant allergens recommended by the Global Allergy and Asthma European Network 10 pollen allergens are included. Complementary other pollen allergens may need to be considered; however, respective awareness may not always be granted. Furthermore, at least in Germany, the situation may be even more complicated by the fact that test allergens need regulatory approval. A decline in commercially available test allergens may result in a diagnostic gap regarding patients with non‐frequent allergies. How many patients with non‐frequent pollen allergies would be affected by this gap? The data presented here partly answer this question. Methods: The study consisted of a descriptive and an analytical part. In the descriptive part, sensitization to frequent pollen allergens (alder, hazel, birch, sweet grasses; according to the German Therapy Allergen Ordinance) and to respective non‐frequent pollen allergens (cypress, Japanese cedar, ash, plane tree, olive, Bermuda grass, wall pellitory, plantain, goosefoot, mugwort, ragweed, and saltwort) was measured in adult patients with physician‐diagnosed allergic rhinitis from two German federal states, namely North‐Rhine Westphalia ( n = 360) and Bavaria ( n = 339), using skin prick testing and/or ISAC technology. Furthermore, respective regional pollen data were assessed. In the analytical part, sensitization data were correlated with each other and with anamnestic data on symptom periods. Results: Sensitization to frequent pollen allergens ranged from 45% (sIgE to Aln g 1/Alder, NRW) to 72% (prick test reactivity to birch, NRW). Sensitization to non‐frequent pollen allergens ranged from 0% (sIgE to Amb a 1/ragweed, NRW) to 41% (prick test reactivity to olive, Bavaria). Sensitization data partly correlated with each other and in connection with symptom periods showed a partly similar seasonal pattern as pollen data. Conclusions: Sensitization to non‐frequent pollen allergens have to be considered when examining patients with respective seasonal symptoms, and test (and respective therapy) allergens for non‐frequent pollen allergies need to be available. Further prerequisites for adequate patient management would be a nationwide pollen monitoring system giving continuous pollen data and a systematic sensitization monitoring at patient level.